B7-H3 as a Target for CAR-T Cell Therapy in Skull Base Chordoma - Long, Cheng; Li, Gaowei; Zhang, Chengyun; Jiang, Tao; Li, Yanjun; Duan, Xin; Zhong, Gang (Frontiers in Oncology, 2021)
Objective: chordomas are rare bone tumors with few therapeutic options. Skull base and sacrum are the two most common origin sites. Immunotherapies are emerging as the most promising approaches to fight various cancers. This study tends to identify new cell surface targets for immunotherapeutic options of skull base chordomas. Methods: we profiled 45 skull base chordoma clinical samples by immunohistochemistry for the expression of six CAR targets (PD-L1, B7-H3, B7-H4, VISTA, HER2 and HER3). In addition, we generated B7-H3 targeted CAR T-cells and evaluated their antitumor activities in vitro. Results: we found that B7-H3 was positively stained in 7 out of 45 (16%) chordoma samples and established an expression hierarchy for these antigens (B7-H3 > HER3 > PD-L1 > HER2 = VISTA = B7-H4). We then generated a B7-H3 targeted CAR vector and demonstrated that B7-H3-CAR T-cells recognized antigen positive cells and exhibited significant antitumor effects, including suppression of tumor spheroid formation, CAR T-cell activation and cytokine secretion. Conclusions: our results support B7-H3 might serve as a promising target for CAR T-cell therapies against chordomas.